Appointment as chairman of working committee – Sarawak Tourist Guide Syllabus, March 2012 - Shaik Hussain, S. A. (Universiti Malaysia Sarawak, 2012)
The Ministry of Tourism Sarawak would like to seek the support of UNIMAS to assist in the upgrading and improvement of the existing tourist guide syllabus.